2020
DOI: 10.1016/j.dam.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Dominating maximal outerplane graphs and Hamiltonian plane triangulations

Abstract: Let G be a graph and γ(G) denote the domination number of G, i.e. the cardinality of a smallest set of vertices S such that every vertex of G is either in S or adjacent to a vertex in S. Matheson and Tarjan conjectured that a plane triangulation with a sufficiently large number n of vertices has γ(G) ≤ n/4. Their conjecture remains unsettled. In the present paper, we show that: (1) a maximal outerplane graph with n vertices has γ(G) ≤ ⌈ n+k 4 ⌉ where k is the number of pairs of consecutive degree 2 vertices se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Conjecture 1 is best possible since, for any planar triangulation G that consists of a triangulation of k vertex-disjoint copies of K 4 embedded so that each copy of K 4 is in the outer face of all other copies of K 4 , we have γ(G) = k = n/4. In spite of the efforts of specialists [7,8,10,11], the best general upper bound found so far for γ(G) is due to Špacapan [13], who proved that γ(G) 17n/53 for every planar triangulation G on n 6 vertices. Observe also that the bound of Conjecture 1 is not satisfied for near triangulations [9, Figure 1].…”
Section: Introductionmentioning
confidence: 99%
“…Conjecture 1 is best possible since, for any planar triangulation G that consists of a triangulation of k vertex-disjoint copies of K 4 embedded so that each copy of K 4 is in the outer face of all other copies of K 4 , we have γ(G) = k = n/4. In spite of the efforts of specialists [7,8,10,11], the best general upper bound found so far for γ(G) is due to Špacapan [13], who proved that γ(G) 17n/53 for every planar triangulation G on n 6 vertices. Observe also that the bound of Conjecture 1 is not satisfied for near triangulations [9, Figure 1].…”
Section: Introductionmentioning
confidence: 99%
“…In the same paper, the authors conjectured that γ(G) ≤ n 4 for every n-vertex triangulation G, when n is large enough. Since then, several papers have been devoted to either trying to prove that conjecture [23,31,34], or showing thigh bounds, mainly for MOPs, for several variants of the domination number [2,3,4,6,7,9,10,19,26,31,35,37]. In particular, Canales et al [3] proved that γ pr (G) ≤ 2 n 4 for any MOP G of order n ≥ 4, and Henning and Kaemawichanurat [19] showed that γ pr2 (G) ≤ 2 5 n for any MOP G of order n ≥ 5, except for a special family F of MOPs of order 9.…”
Section: Introductionmentioning
confidence: 99%